Intergenerational Social Exclusion, Silences, and the Transformation of Agency: An Oral History Approach - Isola, Anna-Maria (Cogitatio Press, 2025)
Abstract:  This oral history article, inspired by research conducted among minorities, explores the interrelations between intergenerational disadvantage, experience of social exclusion, and silence within family histories. During the fieldwork, 13 study participants shared their transgenerational family stories that shed light on intergenerational disadvantage, including substance abuse, trauma, violence, emotional coldness, neuropsychiatric characteristics, and mental health concerns. Study participants had experienced active and passive social exclusion, such as discrimination within service systems, exclusion from the job market, bullying, and discriminatory attitudes. They also believed that their previous generations had experienced social exclusion. This study shows that silence is often a result of the social exclusion experienced by people who deviate from the assumed norm and suffer from disadvantage. To protect themselves from social exclusion, people remain silent. Silence deepens social inequalities by keeping people in weak positions apart and preventing them from acting together to redress power dynamics. Today, however, there are more opportunities than in the past to work on silence and social exclusion, making it possible for these people to shift their positions from being others to being closer to the sources of power.